Smart Education for Corporate Sustainability Reporting - Peter Glavič; Helena Levičnik; Aida Szilagyi; Ibon Zugasti; Thomas Schönfelder; Marek Rosicki; Pavel Ruzicka; Veronika Hajná (Standards)
The European Union’s Corporate Sustainability Reporting Directive expanded its Non-Financial Reporting Directive requirements to companies with over 250 employees, mandating their sustainability reporting from 2025. This expansion will quadruple the number of companies subject to mandatory reporting, presenting new challenges for their managers and responsible employees. Companies will have to report according to the European Sustainability Reporting Standards. This article addresses gaps in vocational education and training (VET) programs related to sustainability knowledge and reporting. It aims to establish a unified approach for VET teachers and learners across the EU, preparing them for the evolving job market demands. The methodology ADDIE (Analysis/Design/Development/Implementation/Evaluation) was used to develop the curriculum and training. The research began by creating a knowledge repository and a questionnaire, focusing on current reporting practices and job requirements, and continued with preparing materials for the training course. The course encompassed six learning units: (1) European legislation and sustainability standards, (2) sustainability management, (3–5) environmental, social, and corporate dimensions, and (6) sustainability reporting. The initiative included multiplier (dissemination) events, pilot applications, and online course tests. To deliver the course effectively, an interactive e-learning platform was developed; gamification elements and other engaging activities were included to enhance learning outcomes.